Penyuluhan Strategi Manajemen Pemasaran Pada Piscok Meler (Studi kasus di Jln. Dempo Raya Simpang Lampu Merah Dehasen Kota Bengkulu ) - utami, Aisyah putri; Yanti, Rina Trisna (Jurnal Dehasen Mengabdi, 2023)
The Piscok Meler business must have strong competitiveness so that the business can survive. From Counseling on Strategy Management Piscok Meler uses descriptive qualitative methods in the form of research or verbal words from the owner and behavior can be very significant. From the owner's response, it was immediately constrained by ingredients that were difficult to find.